e-Generation: A Manual Accounting Practice Set - Pabst, Wendy; Perrin, Brian (John Wiley & Sons, 2014)
e-Generation is a manual accounting practice set for a small company. This practice set provides experience in manually recording and posting a variety of business transactions common to small businesses, so that students gain an understanding of the flow of data in an accounting system. Many of these processes occur out of sight in a computerised accounting system.